Strategi Marketing Public Relations Butik Zaskia Sungkar Dalam Memasarkan Busana Muslim - Desty Aryani; Fatmawati Fatmawati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
This study aims to determine the marketing strategy of public relations Zaskia Sungkar Boutique in marketing Muslim clothing and what social media are used, as well as the advantages and disadvantages in marketing Muslim clothing. The paradigm used in this study is the constructivism paradigm. This study uses a descriptive qualitative approach through interviews, observation and documentation. The results of the study showed that the strategy used by Zaskia Sungkar Boutique in marketing Muslim clothing, namely: pull, push and pass strategies from Thomas L. Harris. This pull strategy prioritizes promotion on social media, and organizes events. This push strategy publishes Zaskia Sungkar's products on social media, e-commerce, and endorsement through public figures. This pass strategy rewards loyal customers by paying attention to the content that will be posted, and maintaining the appearance of Muslim fashion products according to Islamic law.